FRI0350 Evaluation of Cardiovascular and Renal Morbidity in Patients with Gout in Germany, United Kingdom, United States, and France: The International Comorbidity and Resource Utilization Study of Gout (ICARUS). (9th June 2015) - Nuevo, J.; Nyberg, F.; Horne, L.; Morlock, R.; Storgard, C.; Aiyer, L.; Hines, D.; Ansolabehere, X.; Chevalier, P.
Abstract : Background: Hyperuricemia and gout are increasingly prevalent, and if not appropriately treated, may cause permanent joint destruction, bone erosion, and kidney damage. Patients typically have worse-than-normal pre-existing health status at diagnosis, and comorbidities such as chronic renal impairment and cardiovascular (CV) diseases are associated with gout. Objectives: Estimate prevalence and incidence rates (IRs) of potential treatment- or disease-related renal and CV morbidities (pre-existing and new incident events) in patients with established gout in Germany (DE), the United Kingdom (UK), United States (US), and France (FR). Methods: A longitudinal cohort study was conducted using retrospective data from IMS Disease Analyzer™ (DE & FR), Clinical Practice Research Datalink-Hospital Episode Statistics (UK), & IMS' PharMetrics Plus database linked with outpatient laboratory results (US), from Jan 1, 2009 to Dec 31, 2011. Patients were required to have "prevalent established gout" (treated with urate-lowering treatment [ULT] or eligible for ULT based on ACR guidelines) between Jan 1, 2009 & Dec 31, 2009; age ≥18 yrs on index date (Jan 1, 2010); and ≥1 documented visit both prior to Jan 1, 2009 and after Jan 1, 2010. Variable follow-up extended from index date to Dec 31 2011 (all dates +1 yr for FR). Events of interest were identified based on diagnostic codes/laboratory data. Analyses are presented overall and stratified by type of 1st ULT regimen (allopurinol or febuxostat) after index, with follow-up until treatment discontinued. Results: A total of 35, 188 (DE), 24, 607 (UK), 121, 591 (US), and 17, 388 (FR) patients were analyzed. Among renal conditions, baseline diagnosis of CKD/renal failure was most prevalent in the UK (10.9%) & DE (6.7%), whereas prevalence of abnormal serum creatinine (sCR) was most prevalent in the UK (30.6%). Hypertension was the most prevalent CV diagnosis in all 4 countries (59.5% [DE], 24.4% [UK], 52.4% [US], 31.2% [FR]), followed by ischemic heart disease and myocardial infarction (Table ). IRs (per 100 patient-yrs) of new/worsening renal impairment ranged from 1.67 (DE) to 4.34 (US). IRs of nephrolithiasis diagnosis ranged from 0.31 (FR) to 3.79 (US). sCR elevations of 1.5x to <2.0x over pre-index baseline ranged from 0.04 (FR) to 0.61 (DE). Among CV-related rates, incidence of hypertension diagnosis was highest, from 24.4% (UK) to 59.5% (DE), followed by ischemic heart disease. Conclusions: These findings show that gout patients have comorbid renal and CV disease and are at risk for and develop new renal and events. Comorbid illnesses greatly enhance the overall disease burden in this patient population. Awareness and consideration of these comorbidities are important in the medical management of gout patients. References: Zhang W, Doherty M, Bardin T, et al. Ann Rheum Dis. 2011;70:563-570. Kuo CF, Grainge MJ, Mallen C, et al. Ann Rheum Dis. 2014 Nov 14. Grassi D, Ferri L, Desideri G, et al. Curr Pharm Des. 2013;19(13):2432-2438. Acknowledgements: Funding for the study was provided by AstraZeneca. Editorial support was provided by PAREXEL and funded by AstraZeneca. Disclosure of Interest: J. Nuevo Employee of: AstraZeneca, F. Nyberg Employee of: AstraZeneca, L. Horne: None declared, R. Morlock Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., C. Storgard Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., L. Aiyer Employee of: Ardea Biosciences, Inc., a member of the AstraZeneca Group., D. Hines Employee of: IMS Health, X. Ansolabehere Employee of: IMS Health, P. Chevalier Employee of: IMS Health